2019
DOI: 10.1128/aem.01006-19
|View full text |Cite
|
Sign up to set email alerts
|

Heat and Chemical Treatments Affect the Viability, Morphology, and Physiology of Staphylococcus aureus and Its Subsequent Antibody Labeling for Flow Cytometric Analysis

Abstract: The effects of heat and chemical treatments on Staphylococcus aureus viability and physiology and their subsequent effects on antibody binding ability and cell morphology were measured. Treatments included lethal and sublethal heat; exposure to organic acids, salt, and sodium hydroxide; and freeze-thawing. Strain-related differences in viability were noted depending on treatment and were reflected in changes in physiology as monitored by flow cytometry (FCM) using three different staining protocols: SYTO 9/pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…This was in the context of S. aureus NCTC 8325 losing its ability to bind antibody. It could be that the manner of S. lentus and S. xylosus binding to antibody was similar to the damage-mediated, nonspecific binding found in a previous study by this group, where cell damage was shown to increase antibody signal above that of healthy control cells ( 15 ). S. lentus and S. xylosus also displayed the smallest log reductions after incubation on stainless steel compared to the other strains, as measured by plate counting, and FCM data showed that ∼50% of the cells maintained esterase activity.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…This was in the context of S. aureus NCTC 8325 losing its ability to bind antibody. It could be that the manner of S. lentus and S. xylosus binding to antibody was similar to the damage-mediated, nonspecific binding found in a previous study by this group, where cell damage was shown to increase antibody signal above that of healthy control cells ( 15 ). S. lentus and S. xylosus also displayed the smallest log reductions after incubation on stainless steel compared to the other strains, as measured by plate counting, and FCM data showed that ∼50% of the cells maintained esterase activity.…”
Section: Discussionsupporting
confidence: 82%
“…In general, and similar to the data yielded by the surface spiking experiment, permeabilized cells showed greater antibody binding. This points toward a conclusion reached in the Kennedy et al ( 15 ) study, where it was recommended that a cell membrane permeability dye such as PI be used to remove membrane-damaged cells from the final count in FCM antibody-mediated detection assays in order to reduce the problem of false positives.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Furthermore, specific targets such as food pathogens [ 51 ], infectious bacteria [ 52 ], and environmental contaminants are easily detected by FCM combined with phylogenetic labeling. Flow-FISH is a phylogenetic labeling method in which specific nucleic acid sequences inside intact viable cells are labeled [ 53 ], as further discussed in Section 4 .…”
Section: Non-specific State-of-the-art Flow Cytometric Applications For Detection and Monitoringmentioning
confidence: 99%